2000
DOI: 10.1086/318132
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunological Risk Factors Associated withHaemophilus influenzaeType b Conjugate Vaccine Failure in Childhood

Abstract: Haemophilus influenzae type b (Hib) conjugate vaccines have proved extremely efficacious in healthy children. True Hib vaccine failures are rare. Hib conjugate vaccines were introduced for routine immunization in the United Kingdom and the Republic of Ireland in 1992. Coincident with this, active prospective and national surveillance via pediatricians, microbiologists, and public health physicians was commenced to assess the clinical and immunological factors associated with vaccine failure. During the 6 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 28 publications
3
69
0
7
Order By: Relevance
“…La efectividad de la vacunación contra este agente no es 100%, está asociada a la edad del niño, el número de dosis recibidas y las tasas de cobertura vaccinal en la comunidad y factores del hospedero como inmunodeficiencias primarias o secundarias. En esta serie, uno de los dos casos se podría tratar de una falla vaccinal, siendo ésta entendida como el aislamiento de H. influenzae tipo b en un líquido estéril transcurrida una semana o más de la segunda dosis de vacuna en un paciente menor de un año de edad o después de dos semanas de la última dosis de vacuna en pacientes de un año de edad o más 25 . Se necesitaría un análisis completo de la historia clínica en este caso para poder confirmarlo.…”
Section: Discussionunclassified
“…La efectividad de la vacunación contra este agente no es 100%, está asociada a la edad del niño, el número de dosis recibidas y las tasas de cobertura vaccinal en la comunidad y factores del hospedero como inmunodeficiencias primarias o secundarias. En esta serie, uno de los dos casos se podría tratar de una falla vaccinal, siendo ésta entendida como el aislamiento de H. influenzae tipo b en un líquido estéril transcurrida una semana o más de la segunda dosis de vacuna en un paciente menor de un año de edad o después de dos semanas de la última dosis de vacuna en pacientes de un año de edad o más 25 . Se necesitaría un análisis completo de la historia clínica en este caso para poder confirmarlo.…”
Section: Discussionunclassified
“…For those vaccinated after age 12 months, a single dose of any vaccine should be administered [38]. The use of a booster dose is a controversial question and, in the United Kingdom and the Republic of Ireland, the booster dose is not administered [39]. Children < 1 year of age are considered adequately immunized against Hib if, prior to testing, they have received 3 doses of vaccine (when immunization begins before age 6 months) or 2 doses (when immunization begins between 7 and 12 months of age).…”
Section: Discussionmentioning
confidence: 99%
“…[89][90][91] This paper presents summary information on additional medical or immunological risks based on the few publications available containing detailed risk information, from the UK, Canada and Alaska (US) ( Table 1). 20,53,57,92,93 Associated medical conditions reported for children experiencing true Hib country which does not offer routine Hib vaccination, indicated that Hib carriage commenced at age 3-5 mo, peaking at 18-21 mo. 58 Nasopharangeal carriage prior to three months is indicative of high risk or active infection, thus Hib carriage rates can serve as surrogate markers for disease occurrence and risk in some populations.…”
Section: Risks Associated With Hib Carriagementioning
confidence: 99%